EFL Teachers’ Perceptions of Using Graphic Organizers in the Language Classroom - Alfares, Nurah (Advances in Social Sciences Research Journal, 2019)
This study investigates teachers’ perceptions of using graphic organizers (GOs) in the EFL (English as a Foreign Language) classroom. The aim was to explore teachers’ behavior and perceptions regarding the use of GOs in EFL lessons. Mixed qualitative methods were used: classroom observations of six Saudi EFL teachers were conducted to investigate their behavior when using GOs in lessons; reflective reports were obtained from the same six teachers to investigate their perceptions of using GOs in lessons; and the teachers were interviewed to allow their behavior and reflections to be understood in greater depth. The findings show that these teachers found the use of GOs to be beneficial. However, some of them were uncomfortable using GOs, because they struggled to manage their time in class and because the low level of their students prevented them from obtaining the maximum benefits.